A solar actuator based on hydrogen-bonded azopolymers for electricity generation. Issue 8 (8th February 2018) - Xiong, Yubing; Zhang, Lidong; Weis, Philipp; Naumov, Panče; Wu, Si
Abstract : A solar actuator is fabricated by incorporating sunlight-responsive azobenzene into agarose and the sunlight-induced motion is utilized for electricity generation. Abstract : An actuator driven by solar light is developed by incorporating an azo compound (F-Azo) into agarose (AG). The resulting F-Azo-doped AG (F-Azo@AG) films bend under sunlight irradiation. It is demonstrated that the sunlight-induced bending of the F-Azo@AG film transduces the sunlight into electricity when attached to a piezoelectric transducer.